Improved electron transfer of TiO2 based dye sensitized solar cells using Ge as sintering aid - Ahmad, Muhammad Shakeel; Rahim, Nasrudin Abd; Pandey, Adarsh Kumar (Elsevier, 2018)
Low electron mobility of TiO2 semi-conductor and inferior inter-particle contact facilitate recombination reactions that leads to low performance of dye sensitized solar cells (DSSCs). To improve electron mobility at relatively low sintering temperatures, doping of germanium (Ge) nanoparticles with TiO2 have been trailed due to its excellent optoelectronic and low temperature sintering properties. Anatase TiO2-Ge nanocomposites have been prepared by using colloidal suspension process and deposited on conducting glass using doctor blade technique. Four types of nanocomposites i.e. (1) TiO2–0.5 wt%Ge, (2) TiO2–2 wt%Ge, (3) TiO2–5 wt%Ge and (4) TiO2–10 wt%Ge have been prepared and sintered at 400 °C with a control specimen fabricated using pure TiO2 nanoparticles (sintered at 450 °C) for comparison purpose. To investigate the morphological and structural characteristics, SEM and XRD have been employed. The UV-vis and impedance spectroscopy have been performed to observe light absorption and electron transfer characteristics respectively. Finally, specimens were tested for their photo conversion efficiency. An increase in electron transfer ability and conversion efficiency have been recorded with increase in Ge nanoparticles even at 400 °C sinter temperature compared to reference TiO2 photoanodessintered at 450 °C.